La memoria del male. Rimorso, ricordo e oblio nello sviluppo dell’identità etica - Pisano, Aldo (Filosofia Morale/Moral Philosophy, 2024)
This paper focuses on the relationship between memory, forgetting, and moral identity. It analyzes how moral actions influence ethics through thinking. The ‘inner dialogue’ is a crucial process in the individual moral development, especially with regard to the memory of evil actions. Good and evil experiences (factual memory) create representations of good and evil as qualities (value memory) for individuals, while both remembering and forgetting can improve moral judgement and decision-making.